PERAN KADER POSYANDU DALAM PENGAPLIKASIAN STIMULASI, DETEKSI DAN INTERVENSI DINI TUMBUH KEMBANG ANAK DI DESA PUCUNGKEREP KECAMATAN KALIWIRO KABUPATEN WONOSOBO - Adi Wibawa, Yan; -, Herniyatun; -, Sarwono (Jurnal Ilmiah Kesehatan Keperawatan, 2013)
Posyandu (integrated health center) is a monthly routine and simultaneous activity held in villages to encourage the participation of the society in observing  the children growth and elderly health that very important in early detection. Data from Puskesmas (public health centre) of Kaliwiro on 2010 show that there were 14 from 3.736 children experienced growth disorder. Posyandu cadre as a leader of health in the district has a responsibility to observe and to do early stimulation on growth and development to the children appropriate with the Posyandu vision. The research was aimed to find out the role of Posyandu cadre in stimulation, detection, and early intervention for the growth of the children in Pucungkerep village, Kaliwiro sub district, Wonosobo regency. This research is a descriptive qualitative research with fenomenologic approach. The samples were taken by using purposive sampling technique. There were seven partisipans observed in the study. Data were collected by indepth interview and observation. The results of this research have been managed in five themes, they are cadre role before Posyandu activity, during Posyandu activity, after Posyandu activity, problem emerge, and problem solving. The results show that the role of cadre on stimulation, detection, and early intervention are already on the right way according to the themes that have been categorized, but five cadre were doing height measurement and weight measurement only instead of four measurements that already formed by Indonesian ministry of health e.g height measurement, weight measurement, head’s circumference and upper arm circumference. Based on those results above, it is suggested to hold training for Posyandu cadres about  measurement of head’s circumference and upper arm circumference, so that the role of Posyandu cadre on stimulation, detection, and early growth detection can be more effective. Keywords: Health worker role, integrated health center, children growth